Innovation Promotion Rationales and Impacts – A Review - Eero Aalto; Robin Gustafsson (The Research Institute of the Finnish Economy (ETLA), 2020)
We review the extant research on the government innovation promotion rationales and impacts. Based on the research literature, the review synthesizes innovation promotion rationales, economic justifications for the intervention, impact evaluations of innovation promotion interventions, and current forms and mechanisms of innovation promotion. We identify four main rationales and economic justifications for government intervention in promoting research, technology development, and innovation: (1) the market failure rationale; (2) the system failure rationale; (3) policy outcome rationale from positive spill-over effects from research, technology development and innovation; and (4) four mission oriented policy rationale, including grand societal challenges, responsible innovation, demand-side innovation policy, and public sector innovation. Recent impact evaluation evidence show, in general, more positive than negative outcomes from innovation promotion. Research designs still include high degree of heterogeneity, and thus has some mixed results. Studies are still divided on the crowding-out effect, and to which extent interventions translate into long-lasting benefits. We find tentative positive impacts on broader policy goals seeking for societal and economic benefits. Future public policies and impact evaluations should seek to incorporate more holistic and longitudinal designs.
Keywords: L53; O38; O30; 330; Innovation policy; Impact evaluation; Policy rationales; Innovation promotion